The co-crystal structure of 4-chlorobenzophenone–salicylhydrazide(1/1), C20H17ClN2O3 - Wang Ji; Wu Wenhui; Zhang Wencai; Yang Xiying; Qiao Jie (Zeitschrift für Kristallographie - New Crystal Structures)
C20H17ClN2O3, triclinic, P 1‾ $\overline{1}$ (no. 2), a = 6.2486(3) Å, b = 7.4746(4) Å, c = 19.0245(10) Å, α = 89.341(2)°, β = 85.998(2)°, γ = 83.651(2)°, V = 880.94(8) Å3, Z = 2, R gt(F) = 0.0351, wRref (F 2) = 0.0970, T = 289 K.